Imperio y democracia en el pensamiento político griego - Olivera, Diego Alexander (2018)
This article aims at offering some arguments to understand the relationship between empire and democracy in Greek political thought. So, first, I will look into the language about power in the political vocabulary, presenting a thesis based upon a thesis by Nicole Loraux. Then, I will examine Aristotle?s The Constitution of Athens and Politics in order to understand how the Stagirite brings the imperial phenomenon into his political philosophy. Lastly, I will draw the following conclusion: even though Greek political thought did not conceive of empire as in contradiction with democracy, used to rule over the city, it placed the exercise of imperial power in a different site in regards to the power exerted in the democratic polis. Therefore, the fact that democracy was imperial did not amount to a paradox because democracy and empire corresponded to dissimilar domains in the power relations among men.